Cost-Effectiveness of Domestic PD-1 Inhibitor Camrelizumab Combined With Chemotherapy in the First-Line Treatment of Advanced Nonsquamous Non–Small-Cell Lung Cancer in China - Qiao, Liu; Zhou, Zhen; Zeng, Xiaohui; Tan, Chongqing (Frontiers in Pharmacology, 2021)
Objective Camrelizumab is the first domestic PD-1inhibitor approved to be combined with chemotherapy as a first-line therapy for advanced nonsquamous non-small-cell lung cancer (NSCLC) in China. This purpose of this study was to determine whether use camrelizumab in the first-line setting is cost-effective compared with traditional chemotherapy or imported PD-1inhibitor pembrolizumab in China. Material and Methods A Markov model was built to simulate 3-week patients transitions over a lifetime horizon from the perspective of Chinese healthcare system. Health states included stable disease, first progression, second progression and death. Direct comparison between first-line camrelizumab in combination with pemetrexed and carboplatin (CPC) and pemetrexed plus carboplatin (PC) was performed by calculating transition probabilities from the CameL trial. Indirect comparison between first-line CPC and pembrolizumab in combination with pemetrexed and platinum (PPP) was performed by calculating transition probabilities using network meta-analysis. Costs in the Chinese setting were collected from local public database and literatures. Sensitivity analyses explored the uncertainty around model parameters. Results In the primary analysis, first-line CPC gained an additional 0.41 quality adjusted life-year (QALY) with an incremental $3,486 costs compared with PC, which resulted in an incremental cost-effectiveness ratio (ICER) of $8,378 per QALY gained. In the secondary analysis, first-line PPP yielded an additional 0.10 QALYs at an incremental cost of $6,710, resulting an ICER of $65,563 per QALY gained. Conclusion From the perspective of Chinese healthcare system, our findings supported that first-line CPC was a cost-effective treatment strategy compared with traditional PC chemotherapy and the imported PD-1 inhibitor combined with platinum-based chemotherapy (PPP) for advanced nonsquamous NSCLC patients without targetable genetic aberrations. This analysis provided strong evidence for promoting the widespread use of first-line CPC in China, and to some extent stimulated the enthusiasm for the development of domestic cancer drugs.